Normed Domains of Holomorphy - Steven G. Krantz (International Journal of Mathematics and Mathematical Sciences)
We treat the classical concept of domain of holomorphy in ℂn when the holomorphic functions considered are restricted to lie in some Banach space. Positive and negative results are presented. A new view of the case n=1 is considered.